Harris, Peter James. From Stage to Page: Critical Reception of Irish Plays in London Theatre, 1925-1996 - O'Brien, Paul (ABEI Journal, 2011)
Harris, Peter James. From Stage to Page: Critical Reception of Irish Plays in London Theatre, 1925-1996. Oxford: Peter Lang, 2011.